Canciones de peregrinos franceses del Camino de Santiago: temática y funcionalidad - Iñarrea las Heras, Ignacio (Revista de Filología Románica, 2006)
From a thematic standpoint, this article offers a panoramic view of the French popular songs within the context of the Jacobean pilgrimage. It proposes a classification and an analysis of these songs which revolves around their content and aims. Furthermore, the author attempts to show that their variety and richness is a consequence of the religious interest and the cultural importance that the universe of the Jacobean belief system reached in the past.